Health-Related Quality of Life in the Gender, Race, And Clinical Experience Trial - Judith Feinberg; Michael Saag; Kathleen Squires; Judith Currier; Robert Ryan; Bruce Coate; Joseph Mrus (AIDS Research and Treatment)
Background. We report health-related QoL (HRQoL) from GRACE (Gender, Race, And Clinical Experience) study by sex and race over 48 weeks. Methods. 429 treatment-experienced adults (HIV-1 RNA≥1000 copies/mL) received darunavir/ritonavir 600/100 mg twice daily plus an appropriate background regimen. QoL was measured by the Functional Assessment of HIV Infection (FAHI) questionnaire. Results. 67% women and 77% men, including 67.4% black, 76.0% Hispanic, and 73.8% white patients, completed the trial. Baseline total FAHI scores were similar between sexes and races. Total FAHI of the entire population improved by Week 4 (𝑃<.05); near-maximum changes obtained by Week 12 were maintained through Week 48. Women and black patients demonstrated larger improvements in total FAHI versus men, and Hispanic and white patients, respectively. Conclusion. HRQoL improved in all sex and racial/ethnic groups. Sex-based and race-based differences in improvements in FAHI subscales may provide insight into subtle differences of HIV-1 and treatment on HRQoL in different populations.